New Leptocheliidae (Crustacea: Tanaidacea: Tanaidomorpha) from Australian seagrass and macro-algal habitats, and a redescription of the poorly-known Leptochelia ignota from Sydney Harbour - Edgar, Graham J. (Zootaxa, 2012)
Australia possesses a rich fauna of leptocheliid tanaidaceans (Crustacea: Tanaidacea: Leptocheliidae), including manyspecies that currently remain undescribed. As an addition to the 13 leptocheliid species known to date from Australianwaters, a new genus (Poorea n. gen.) and five new species collected from shallow macrophyte habitats are diagnosed(Parakonarus robertsoni n. sp., Leptochelia evansi n. sp., Leptochelia gadgeti n. sp., Poorea wrighti n. sp. and Pooreajohannesi n. sp.). Leptochelia nobbi is transferred to the genus Poorea, Leptochelia fairgo to Parakonarus, and a rede-scription provided for the enigmatic tanaidacean Leptochelia ignota on the basis of specimens collected near the Sydney type locality. A key is provided to Australian leptocheliid species.